PENGUATAN KAPASITAS TUGAS DAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DESA POPISI - Sandewa, Fadli; Sibay, Sahraen; Zaman, Wildan; Karateng, Muzakir Dg.; Amelia, Sinta; Towendo, Aditia S; Lajaiya, Uun Erawati; Maladjuna, Riski A.; Maddatu, Abdi Gunawan; Rahmat, Moh. Rival; Kurniawan, K; Malik, Al; Jainahu, Risman (FKIP Universitas Samawa, 2024)
Kegiatan sosialisasi dengan judul